Effective and Catalyst-Free Preparation of Thiazolidines via Novel [3+2] Annulation of 1,4-Dithiane-2,5-diol and Benzothiazolimines - Liu, Min; Zhao, Lin-quan; Song, Xiang-jia; Lu, Jin-rong; Cui, Wen-quan (Synlett, 2025)
A novel [3+2] annulation of 1,4-dithiane-2,5-diol and benzothiazolimines has been developed for the efficient, one-step preparation of highly sterically demanding thiazolidines in excellent yields (up to 99%) and moderate diastereoselectivities (1:1 to 2.4:1) under mild conditions within a few minutes. A series of thiazolidines compounds were obtained and a scaled-up experiment was conducted with excellent results. The absorption, metabolism, and toxic (ADMET) properties of the compounds were evaluated with good results, demonstrating the potential applications of this protocol.
Keywords: [3+2] annulation; 1,4-dithiane-2,5-diol; benzothiazolimines; thiazolidines; ADMET